Studies of Asilidae (Diptera) systematics and evolution: I. A preliminary classification in subfamilies - Papavero, N. (Arquivos de Zoologia, 1973)
A preliminary classification of the Asilidae in 8 subfamilies is proposed: Apocleinae (55 genera), Asilinae (62 genera), Dasypogoninae (70 genera), Laphriinae (69 genera), Laphystiinae (23 genera), Ommatiinae (7 genera), Stenopogoninae (102 genera), and Trigonomiminae (12 genera). A brief diagnosis of the subfamilies, a list of their respective genera, plus their general geographic distribution and hypothetical phylogeny, are given.